Absolutely one thing : featuring Charlie and Lola - Child, Lauren (Child, Lauren. Charlie and Lola., 2016)
Charlie and Lola choose a single treat at the store, count ladybugs, note the lateness of the time, and are introduced to other simple math concepts.